Who is solving the challenge? The use of ChatGPT in mathematics and biology courses using challenge-based learning - Elizondo-García, Mariana E.; Hernández-De la Cerda, Héctor; Benavides-García, Ingrid G.; Caratozzolo, Patricia; Membrillo-Hernández, Jorge (Frontiers in Education, 2025)
The advent of Artificial Intelligence has revolutionized how students can solve academic assignments. In particular, the Conditional Generative Pretrained Transformer, ChatGPT, has become a powerful tool for generating quick solutions to academic assignments in higher education. However, we are still at the beginning of its use and do not yet know the scope or consequences that this will bring to developing both disciplinary and transversal graduation competencies. Here, we report a pilot study in two digital subjects in higher education with the resolution of activities using ChatGPT. The students were exposed to carrying out these assignments individually, and then they verified the quality of their work with traditional sources of high academic quality. After surveying what they experienced, some declared that this was their first time using ChatGPT, while others had already used the tool. The tool has many advantages for the student, such as the immediacy of the information, ease, and availability. However, many concerns arose about the veracity and depth of the topics covered and discomfort based on whether the tool would supplant the teacher or whether the development of skills and competencies would be affected. The need for urgent modifications to the code of academic integrity and the application of new ethics for the use of AI is clear. Our results indicate that teachers should be prepared to use AI expeditiously and that detectors for text generated by AI should be available for evaluation on using this powerful tool.